A formação e a atuação do profissional fisioterapeuta: um estudo com egressos da UFMG - 1982-2005 - Ana Maria Chagas Sette Camara Ribeiro (2006)
In this researches, sought itself contribute for better clarity and bigger deepening of the arguments about the trial of formation and professionalization of the formed physiotherapist in the UFMG. For so much, it analyzed itself the evaluation that the graduate of the Physiotherapy Graduation course of the UFMG do of the course, as well like of his professional journeys and the relations that can be established between both. It opted by a cross study kind survey, with self-applicable questionnaire in graduate selected by the approach of sample stratified. The sample was calculated from the total population of 828 ex- students, graduate between December of 1982 to January of 2005. The total size of the sample calculated in this I study was of 92 graduate, being 27 in the Stratum 1, 31 in the Stratum 2 and 34 in the Stratum 3. In the fact-gathering of this I study were approached the following aspects: identification and contacts; studies after graduation; professional activities; labor market; evaluation of the course of graduation. The questionnaires were car-administered, envoys by email and by the mail. The facts obtained were stored in a database and organized with the statistical application SPSS, of current use in the social sciences. Studies in the field of the sociology of the professions and in the area of curriculum substantiate this work and constitute the reference for the analysis of the facts. The results obtained show, by a side, that the course of graduation in Physiotherapy of the UFMG not alone achieved his initial objective of attend to the demand of form professionals for act in the rehabilitation, as had important participation in the construction of the identity of the profession in General Mines, having impact in the external and internal representation to the group, extending and delimiting borders of the field of. On the other hand, establishes-itself that, second the evaluation of the ex-students, is a course of traditional pedagogical practices, structured in the model of the technical rationality, without a broader space of insertion of the students in the reality of the future professional practice. The facts show, still, that the majority of the formed professionals in the UFMG is of the female sex, with medium age of 34 years, having studied the postgraduation in levels of specialization and/or master, working big part in institutions of higher education and in functions of management in the public service and in the private sector. It is inserted in the labor market, satisfied with his professional activity and recognizes that introduces technical news and forms of action in the labor market. Practically all of the ex students said to be in activities related with the physiotherapy and evaluate that is worth hardly be a physiotherapist. The facts suggest also that the possibilities of work for the graduate in Physiotherapy by the UFMG are enough broad.